Leaf wax biomarkers in transit record river catchment composition. Issue 18 (24th September 2014) - Ponton, Camilo; West, A. Joshua; Feakins, Sarah J.; Galy, Valier
Abstract Rivers carry organic molecules derived from terrestrial vegetation to sedimentary deposits in lakes and oceans, storing information about past climate and erosion, as well as representing a component of the carbon cycle. It is anticipated that sourcing of organic matter may not be uniform across catchments with substantial environmental variability in topography, vegetation zones, and climate. Here we analyze plant leaf wax biomarkers in transit in the Madre de Dios River (Peru), which drains a forested catchment across 4.5 km of elevation from the tropical montane forests of the Andes down into the rainforests of Amazonia. We find that the hydrogen isotopic composition of leaf wax molecules (specifically the C28n‐alkanoic acid) carried by this tropical mountain river largely records the elevation gradient defined by the isotopic composition of precipitation, and this supports the general interpretation of these biomarkers as proxy recorders of catchment conditions. However, we also find that leaf wax isotopic composition varies with river flow regime over storm and seasonal timescales, which could in some cases be quantitatively significant relative to changes in the isotopic composition of precipitation in the past. Our results inform on the sourcing and transport of material by a major tributary of the Amazon River and contribute to the spatial interpretation of sedimentary records of past climate using the leaf wax proxy.